Challenges and best practices in training teachers to utilize artificial intelligence: a systematic review - Aljemely, Yousef (Frontiers in Education, 2024)
The utilization of artificial intelligence is becoming a hot debate among researchers, academicians, and practitioners. Educational institutions are also training teachers to utilize AI in teaching. However, there is a dearth of investigation on the training of teachers to utilize AI. Therefore, this systematic review aims to highlight the challenges and best practices in training teachers to utilize AI. Strict inclusion and exclusion criteria were set to shortlist the relevant studies for review. The review synthesized 10 studies focusing on the importance of AI, AI usage by teachers, challenges faced by teachers and trainers, and best practices that could be adopted by trainers. The results highlighted teachers lack the motivation for AI utilization and it is the biggest challenge faced by the trainers. Therefore, the training programs should be motivating, customized, and highlight the importance of AI. Moreover, the training sessions should also provide a trial of the latest AI technologies to the teachers so that they can get hands-on experience. This review can help AI trainers design customized training programs for teachers by keeping in mind the challenges faced by them. An effective training program can be designed if a trainer is aware of potential challenges faced by trainees. Thus, this research has not only discussed the challenges but also provided guidelines for AI trainers training teachers.